IMPORTANCE OF EARLY DIAGNOSIS IN SMALL BOWEL PERFORATION FOLLOWING BLUNT ABDOMINAL TRAUMA: A CASE REPORT (Journal of Forensic Medicine & Toxicology, 2025)
Intestinal perforation resulting from blunt abdominal trauma presents diagnostic challenges and carries significant morbidity and mortality risks if not promptly recognized and managed. We present a case report of a 38-year-old man involved in a two-wheeler accident, who initially showed no signs of severe injury but deteriorated rapidly within 24 hours, leading to a fatal outcome upon arrival at a tertiary care center. Post-mortem examination revealed a jejunal perforation with histopathological findings of underlying transmural inflammation and unexpected submucosal fat deposition. This case underscores the importance of early identification and intervention in small bowel perforations following blunt abdominal trauma, particularly in cases of delayed symptom onset. The complexity of traumatic bowel
Keywords: Small Bowel Perforation; Blunt Abdominal Trauma